Gender Empowerment Model in Environmental Management to Control Climate Change - Widiyanto, Agnes; Suratman; Oktavana, Gita; Amelia, Selri (Public Health of Indonesia, 2025)
Background: Climate change is an inevitable consequence of inadequate environmental protection. Strengthening gender roles and functions offers a strategic approach to mitigating its impacts. Objective: This study aims to explore environmental management practices at the micro level through a gender-based perspective. Enhancing the role of gender in addressing climate change can be achieved by improving knowledge and awareness of environmental issues and their associated impacts. The consequences of climate change on public health are frequently observed, particularly through drought, reduced food availability, and limited access to clean water. Methods: This study employs a qualitative research design to gain a holistic understanding of the phenomena experienced by the research subjects. The participants in this study, referred to as informants, were selected to represent diverse perspectives within the community. Results: The primary informants in this study consisted of women and community leaders, while supporting informants included members of the Banyumas Regency community. The community's actions extend beyond environmental protection, encompassing both individual and collective efforts in environmental management. Strengthening gender roles within families demonstrates the shared responsibilities of parents, children, and other community members in fostering environmental stewardship. Effective climate change mitigation is supported by the availability of adequate facilities and infrastructure, as well as systematic models and processes for environmental management and control. Addressing public and environmental health issues remains a critical priority to prevent the widespread impacts of climate-related challenges. Conclusion: Family engagement plays a pivotal role in enhancing knowledge, attitudes, and practices that contribute to climate change mitigation, emphasizing the importance of collaborative efforts at the household and community levels. Keywords: climate; environment; health; community; management